1965 Transactions of the third International Vacuum Congress. 28 June-2 July 1965, Stuttgart, Germany - Adam, Hermann, Dr. phil (Symposium Publications Division, Pergamon Press, 1967)
Sessions 9-13 discusses subjects in the field of cryogenics, vacuum metallurgy, sputtering, gettering, adsorption, desorption, and space simulation. The development and functional description of a cryo pump is covered in the first section of the book. The second section covers the measurement of the pumping speed of a cryo surface cooled with liquid nitrogen. The third topic is the examination of the cryo-getter pump. The van Arkel method is the transformation of a crude metal to a halogen compound. This method is broadly covered in the volume. A section of the text focuses on the production.